ANALISIS UNJUK KERJA AGITATOR BLADE HELICAL RIBBON UNTUK PENGADUKAN BAHAN BAKU BIOGAS - Ilham Dwi Arirohman; Shintha Sarmila A.S Yahya; Lathifa Putri Afisna (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2022)
Biogas is an affordable source of alternative energy. Regarding to increase the yield of biogas production, several studies have implemented a stirring process, one of which is a mechanical stirring process. This study aim to design, manufacture and determine the effect of the agitator blade helical ribbon on the homogenity of biogas slurry. The design parameters considered include force, torque, and power to drive the agitator. Parameters for agitator performance tests were stability of rotation speed and total dissolved solids (TDS) from a mixture manure and water. The designed agitator has a stirring force of 372.849 N, a stirring torque of 8.203 N.m, and the power required to drive the agitator is 143.491 watts or 0.192 HP. The average TDS ratio at 10 rpm rotational speed is 1.35 with a standard deviation of 0.20; at a rotational speed of 30 rpm, the average TDS ratio was 1.37 with a standard deviation of 0.07; and at a rotational speed of 50 rpm the average TDS ratio is 1.8 with a standard deviation of 0.04. The higher the agitator rotation speed, the higher the TDS slurry ratio. The higher the value of the TDS ratio, the more effective the stirring process. The smaller the standard deviation of the TDS ratio value, the more homogeneous the slurry in the biodigester.